Corrosion behavior, mechanical properties, and in-vitro biocompatibility of cast Mg–3Zn–xSi biodegradable alloys for bone regeneration - Engie M. Safwat; Rania E. Hammam; M. E. Moussa; Soha A. Abdel-Gawad; Madiha Shoeib; Shimaa El-Hadad (SN Applied Sciences, 2023)
Abstract In this research, Mg–3Zn–xSi (x = 0, 0.1, 0.3, and 0.6 wt%) biodegradable alloys were produced by simple stir casting method, their microstructure and phase changes were evaluated using X-ray diffraction (XRD), optical microscope (OM) and scanning electron microscope coupled with energy dispersive x-ray analysis (SEM–EDS). Potentiodynamic polarization was conducted to measure the alloys’ corrosion behavior in simulated body fluid (SBF). Tensile strength test and in-vitro biocompatibility evaluation regarding MTT cytotoxicity, ALP osseointegration assay and MG-63 cell growth pattern were conducted. Electrochemical investigations showed that Mg–3Zn alloys enclosing Si attained degradation rates suitable for structural support until bone healing, while the Mg–3Zn alloy without Si had a corrosion rate of 0.128 mm/year which is much lower than the required value. None of the inspected alloys exhibited a significant cytotoxic effect, meanwhile, Mg–Zn base alloy and the alloy with 0.3 wt% Si demonstrated the highest ALP level. The optimum cell growth pattern was demonstrated for Mg–Zn base alloy and the alloy with 0.1 wt% Si. Evidence of calcium phosphate precipitation was observed in the four investigated Mg–3Zn alloys. Therefore, based on the fore mentioned results, Mg–3Zn–xSi alloys were suggested as viable biodegradable materials due to their compatible degradation rates, proved cytocompatibility, high cell viability and excellent osseointegration potential.